Pelaksanaan Keterampilan Bertanya pada Pembelajaran IPS Kelas V di SD Inpres Waioti - Sonya Kristiani Maria (Journal on Education, 2023)
The implementation of education in schools involves teachers and students to carry out teaching and learning activities and to interact with each other. The researcher conducted by the author in this study is qualitative research. Qualitative research is a research method based on postpositivise philosophy, used to research on natural object conditions, (as opposed to experiments) where the researcher is the key instrument, collection techniques with triangulation (combined), data analysis is inductive / qualitative, and qualitative research results emphasize meaning rather than generalization. The results showed (1) The implementation of basic and advanced questioning skills in social studies class V at SD Inpres Waioti has mastered the skill of asking quite well (2) Student response in the implementation of basic and advanced questioning skills in social studies class V at SD Inpres Waioti is very good.